STUDENTS’ DIFFICULTIES IN READING COMPREHENSION OF FACTUAL REPORT TEXT AT THE ELEVENT GRADE OF SMK NEGERI 2 TOMA - Harita, Magdalena (Universitas Nias Raya, 2024)
This research was carried out to investigate students’ difficulties in reading comprehension of factual report text at the eleventh grade students of SMK Negeri 2 Toma. The objectives of this research were to find out what difficulties are faced by class XI students at SMK Negeri 2 Toma in reading comprehension of factual report text and to explain the factors that contribute to students’ difficulties in reading comprehension of factual report texts in class at SMK Negeri 2 Toma. This research was qualitative research design and data were obtained through reading tests and interviews. Data were analyzed using Miles and Huberman's theory such as data reduction, data display and conclusion drawing and verification. The results of this research were eleventh grade students at SMK Negeri 2 Toma experience difficulties in reading comprehension. It was found that five difficulties experienced by students in reading comprehension they are finding factual information, finding the main idea, finding the meaning of vocabulary, identifying references and making inferences. Factors that contribute to students’ difficulties in reading comprehension of factual report texts include limited vocabulary knowledge, inadequate use of effective reading strategies, and problems with processing information. This research shows that students experience difficulties in reading comprehension. It is suggested that students eleventh grade of SMK Negeri 2 Toma should study more the component of reading comprehension.